The Link Class Project: Collaborative virtual teams between Peru and The Netherlands - Olivos Rossini, Mariella (2015)
The Link Class Project presented in this article provides an example of established collaborative group activities to negotiate and build a report together in virtual teams composed of students at Universidad ESAN, Lima (Peru) and Tilburg University, Tilburg (Netherlands). Itfurther analyzes the effects of a campus based internationalization strategy supported by the use of technology. Based on previous experiences with virtual classrooms, the authors adhere to the ancient Chinese philosopher’s, Lao Tzu, quote: «If you tell me, I will listen; if you show me, I will see; but if you let me experience, I will learn» Doi: http://dx.doi.org/10.1016/j.jefas.2015.10.001